1995
DOI: 10.1080/02827589509382897
|View full text |Cite
|
Sign up to set email alerts
|

Stand biomass dynamics of pine plantations and natural forests on dry steppe in Kazakhstan

Abstract: Biomass dynamics were studied in isolated relict stands of scots pine (Pinus sylvestris) on the dry steppe of Kazakhstan (53-54°N) where potential evaporation is 500-600 mm yr -1 and the rainfall is 250-260 mm yr -1 . Samples were taken from 7 plots in natural stands on sandy forest soils (age 13-110 years) and 10 plots in plantations on dark-chestnut-coloured soils (age 5-50 years). Nine or 10 sample trees were taken from each plot, giving a total of 68 and 96 sample trees in natural and plantation stands res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 3 publications
3
11
0
1
Order By: Relevance
“…Following an initial increase with stand age, foliage biomass appeared to reach a peak at age 10-20 years before a gradual decline to a stable level at a much later stage. This pattern is consistent with the pattern described above and well recognized age-related changes in leaf area index and decline in stand productivity (Usol'tsev and Vanclay, 1995;Magnani et al, 2000;Köstner et al, 2002). The comparison between the individual tree biomass equations of Baker et al (1984) and the Australian system of additive equations highlighted the limitations of scaling up foliage biomass estimates from individual trees to stands.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Following an initial increase with stand age, foliage biomass appeared to reach a peak at age 10-20 years before a gradual decline to a stable level at a much later stage. This pattern is consistent with the pattern described above and well recognized age-related changes in leaf area index and decline in stand productivity (Usol'tsev and Vanclay, 1995;Magnani et al, 2000;Köstner et al, 2002). The comparison between the individual tree biomass equations of Baker et al (1984) and the Australian system of additive equations highlighted the limitations of scaling up foliage biomass estimates from individual trees to stands.…”
Section: Discussionsupporting
confidence: 84%
“…The parameter associated with stand height for bark biomass was constrained to be the same as for stem wood biomass to overcome the effects of the high degree of multicollinearity among the predictor variables on the unconstrained parameter estimates. The transformations of stand age for stem wood, bark and foliage biomass in the model specification was to reflect age-related patterns in basic stem wood density of P. radiata as demonstrated by Cown et al (1991), Tian et al (1995) and Raymond and Joe (2007), and also age-related changes in leaf area index as described by Usol'tsev and Vanclay (1995), Magnani et al (2000) and Köstner et al (2002). The transformations were selected from several alternative forms following repeated fitting and comparisons in order to improve the biological realism in the final model specification as advocated by Vanclay and Skovsgaard (1997).…”
Section: Model Specification and Estimationmentioning
confidence: 98%
“…in the oak-beech stand and ash in the ash stand, accounted respectively for 84.0% and 66.4% of the total aboveground carbon stock. Carbon storage in the aboveground biomass of the Aelmoeseneie forest is comparable with the values found in previous studies [6,15,27,34,41]. Dutch investigators [25] showed that the carbon stock in living biomass is largest for beech forests, a conclusion comparable to results found here.…”
Section: Aboveground Carbon Poolssupporting
confidence: 82%
“…The carbon stocked in the tree layer varies widely: from 23 to 82% of the total ecosystem carbon pool [6,27,41], and this depends highly on the tree species. The tree compartment itself can be split up in an above-and belowground part, and further in leaves, branches and stems and fine and coarse roots respectively.…”
Section: Introductionmentioning
confidence: 99%
“…An increased below‐ground allocation has also been proposed as a possible explanation, as a consequence of the reduced availability of nutrients that are increasingly immobilized in litter during stand development ( Murty, McMurtrie & Ryan 1996). A greater fine root‐to‐foliage biomass ratio with age has indeed been often observed ( Grier et al 1981 ; Santantonio 1989; Ryan & Waring 1992; Usol’tsev & Vanclay 1995; Vanninen et al 1996 ).…”
Section: Introductionmentioning
confidence: 84%